Nineteen Eighty-Four: The (Ir)Rational Dystopia - Melita Drnasin; Denis Kuzmanović (Društvene i Humanističke Studije, 2025)
The reputation of Orwell’s Nineteen Eighty-Four speaks for itself, both in the genre of political dystopia and the mainstream consciousness. People are usually familiar with some of its well-known ideas, like: “Big Brother”, “doublethink”, “2+2=5” and “Thought Police” even if they have not read the novel itself. Those who did, especially when it was published in 1949, in the tense aftermath of WW2, generally saw the novel as a prophetic, cautionary tale of a very possible future if totalitarianism was allowed to spread unopposed. For later readers, even when the political situation in the West did not slide into tyranny, the novel’s feeling of dread remained, and it became not only a by word for totalitarianism but also for many political and social ills of their time. Much of the novel’s setting and politics appear plausible and relevant as it is based on real totalitarian societies and is not set in a far-away futuristic society. There is, however, a different dimension to it, revealed after a deeper examination of Oceania’s totalitarian oligarchy, and that is irrationality, insanity, or, more precisely, satire, where the Party’s oppression seems beyond excessive, even ridiculous; this can undermine its realism and plausibility as a political dystopia. This is mainly due to doublethink, a notion where indoctrinated people are supposed to hold two opposite ideas and believe in both as true, and Newspeak, a government mandated simplified artificial language which is supposed to limit people’s very thoughts. Viewed from this perspective, the oppression in the novel becomes implausible, preposterous, unreal. This interplay of realism and irrationality, plausibility and satire, can make the novel simultaneously frightening and comforting, a sort of a conflicting, doublethink experience itself. The purpose of this essay is to investigate if realistic (plausible) or irrational (satirical) elements of Nineteen Eighty-Four are more dominant; the prevalence of the former would make it a classical political dystopia, as it is generally perceived, while the dominance of the latter would make it a satirical nightmare, where its status as a cautionary tale would be diminished. Through close reading of the novel’s main political ideas, the conclusion this discussion reaches is that the irrational power of doublethink, along with certain other elements, make the novel less convincing as a classical political dystopia due to its dominant satirical aspect.